Satisfaction level of users on green building office in Putrajaya using post occupancy evaluation / Nur Akma Mohd Zaidon - Mohd Zaidon, Nur Akma (Faculty of Architecture,Planning and Surveying, 2014)
Green building office is one of the important elements of the sustainable development in Malaysia. Green Buildings are referred to as those that are capable of reducing the negative effects of development on the environment and human health with the aim of promoting sustainable life. This study aim is to improve green building office criteria once encounter user’s satisfaction level by using post occupancy evaluation (POE) methods. With this aim, we can find the occupants evaluation on the green building office and also to determine either the green building office elements convinced for occupants satisfaction. Green building office at Putrajaya has been selected as case study using a questionnaire approach. 75 questionnaires have been distributed to the occupant in green building office which is more focus on the green building office evaluation and satisfaction level. Interview session with competent persons will also be conduct to support the finding in questionnaire session. Therefore, the end of this research based on data wasgathered factors that influence building occupancy evaluation on green building office, analysis post occupancy evaluation towards the green building office performance and way to approach and convince green building’s occupants can be determined, identify and discover.